SISTEM PELAYANAN ADMINISTRASI KEPEGAWAIAN DI BADAN PENDAPATAN DAERAH KOTA JAYAPURA - Iek, Daud Emerson (Universitas Cenderawasih, 2023)
The purpose of this study was to determine the personnel administration service system at the Jayapura City Regional Revenue Agency. The urgency of this research lies in the importance of ensuring the effectiveness and efficiency of personnel administration as the main support in improving the performance of government organisations. The research method used in this study is descriptive qualitative with data collection techniques through interviews, observation, and document analysis. This approach allows the researcher to gain an in-depth understanding of the personnel administration process in the agency under study. With good administrative services, all matters related to staffing can be carried out systematically, the administrative process becomes smooth, and can support optimal employee performance. The results showed that the General and Personnel Subdivision of the Jayapura City Regional Revenue Agency runs a personnel administration service system through collecting, verifying, checklist, and decision-making activities. In collecting employee data, two methods are used, namely manual and electronic, including data such as promotion decrees, periodic salaries, service notes, employment agreements, and lists of retired employees. This sub-section also prepares materials and manages the administration of the rank order list and employee files, so that all matters related to personnel administration can be organised effectively and efficiently.